Hegemoni Media Sosial Sebagai Sumber Informasi Pesan-Pesan Dakwah Di Era Digital - Sopiyan, Wawan; Nurrohman Zulkarnain; Erik Yuyanda; Muhammad Rendiko Efritiansyah; Cahaya Fatimah Qurrata'ayun (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
The development of information technology in the digital era has significantly changed the landscape of Islamic preaching. Social media, with its wide reach and high interactivity, has now become a primary source of religious information for the public. This study aims to analyze the hegemony of social media in shaping the perception, understanding, and acceptance of Islamic preaching messages in the digital space. The research method used is a qualitative approach using literature study techniques and content analysis of various social media platforms. The results show that social media not only serves as a channel for distributing Islamic preaching messages but also as an arena for forming discourse influenced by algorithms, the popularity of public figures, and digital trends. This hegemony implies a shift in religious authority from formal institutions to popular figures on social media, which can both enrich and pose challenges to the authenticity and depth of Islamic preaching messages. These findings emphasize the importance of digital literacy and critical thinking in consuming religious information in the modern era.